1998
DOI: 10.1111/j.1530-0277.1998.tb03903.x
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Approach and Avoidance Learning in Alcohol‐Preferring and Alcohol‐Nonpreferring Rats

Abstract: Although numerous biochemical and physiological differences have been shown to be correlated with alcohol preference, less is known about behavioral factors that may correlate with alcohol preference. Using a signaled barpressing task, alcohol-preferring (P; n = 18) and alcohol-nonpreferring (NP; n = 19) rats were compared for their ability to learn an appetitive and an aversive task. Results showed that P rats had difficulty learning the tasks in comparison with NP and nonselected, control rats when appetitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…While the HAD2s’ behavior was also associated with high levels of free access alcohol drinking, they were characterized by passive avoidance and an increased latency to explore a novel environment. Salimov () ultimately characterized the P rats as having “alcohol drive with novelty seeking and persistence,” while the HAD rats have “alcohol drive with timidity and meekness.” Similarly, HAD2s, but not P rats, have been seen to possess an avoidance (but not appetitive) learning deficit that may be due to increased anxiety (Blankenship et al., , ). This view is supported by findings that the HAD2s avoidance learning deficit is decreased with moderate levels of alcohol, presumably via its anxiolytic effects (Rorick et al., ), and the HAD2s have increased heart rate reactivity in a Pavlovian fear conditioning paradigm (Rorick et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…While the HAD2s’ behavior was also associated with high levels of free access alcohol drinking, they were characterized by passive avoidance and an increased latency to explore a novel environment. Salimov () ultimately characterized the P rats as having “alcohol drive with novelty seeking and persistence,” while the HAD rats have “alcohol drive with timidity and meekness.” Similarly, HAD2s, but not P rats, have been seen to possess an avoidance (but not appetitive) learning deficit that may be due to increased anxiety (Blankenship et al., , ). This view is supported by findings that the HAD2s avoidance learning deficit is decreased with moderate levels of alcohol, presumably via its anxiolytic effects (Rorick et al., ), and the HAD2s have increased heart rate reactivity in a Pavlovian fear conditioning paradigm (Rorick et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of response onset and total number of bar-presses performance revealed no significant differences between the three groups. As in previous studies with other strains of rats (Blankenship et al, 1998;Steinmetz et al, 1993), during avoidance training, the LAD1 and N/Nih rats provided well-timed avoidance responses just prior to shock onset. In the appetitive condition, all rats responded soon after tone onset.…”
Section: Response Percentagesmentioning
confidence: 60%
“…Interestingly, the performance of HAD1 and HAD2 rats on the avoidance task differ greatly from the performance of P rats. We previously reported that there were differences in the behavioral performance of P and NP rats on these tasks, relative to Wistar rats, but that the difference was strongly dependent on the order of training given (Blankenship et al, 1998). When appetitive training was given first, the P rats showed retarded rates of learning the appetitive tasks relative to the NP and Wistar rats as well as a retarded rate of learning the avoidance task when the aversive training was given second.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations